Tinjauan Hukum Islam Terhadap Praktik Hutang Piutang Pada Masyarakat Petani Padi - Abdul Hamid (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2021)
The purpose of this study was to find out how Islamic law reviews the practice of debt and receivables in rice farming communities in Sukamantri Village, Tanjungkerta District, Sumedang Regency. This study uses a qualitative approach with case study methods and collects detailed and in-depth information using several data collection procedures during the period. certain. The results of this study indicate that the practice of debt and receivables in the rice farming community and rice dealers in Sukamantri Village, Tanjungkerta District, Sumedang Regency is contrary to Islamic law. However, in the practice of accounts payable, there is an additional that has been promised at the beginning by the rice farmer (creditor) and in additional delivery if it cannot pay off the debt, the addition is first given in the form of rice each time it is harvested.